A importância da educação financeira no planejamento empresarial para microempreendedores: estudo de casos com comerciantes de açaí - FONSECA, Rafaela Amaral da (2023)
This article was developed with the objective of analyzing the influence of financial education in the management of enterprises. Through this approach, it was noticed that the segment of micro and small entrepreneurs only grows in the labor market nowadays, reason for which these will be the subjects of this research, among which we can mention those who work with the commercialization of açaí, fruit this very consumed in the Amazon region. In this way, a data collection was carried out through an interview with five entrepreneurs in the field, residents of the city of Abaetetuba-PA. The information obtained through data collection enabled the contextualization of the idea defended in this study with the reality of these micro-entrepreneurs, in order to obtain relevant conclusions for the study.